May Measurement Month 2018: an analysis of blood pressure screening results from Nigeria. (28th August 2020) - Wahab, Kolawole W; Kolo, Philip M; Sani, Mahmoud U; Okubadejo, Njide U; Peter, Johnson O; Aigbe, Fred; Makusidi, Muhammad A; Aje, Akinyemi; Adewale, Arimiyau; Adebola, Phillip; Beaney, Thomas; Ster, Anca Chis; et al.
Abstract: Hypertension remains the dominant cardiovascular risk factor worldwide. May Measurement Month (MMM) is an annual global programme of the International Society of Hypertension aimed at screening for undetected hypertension in the general population. We report the outcome of MMM 2018 in Nigeria. An opportunistic screening of adults aged at least 18 years was conducted in the six geopolitical zones of Nigeria in the month of May, 2018. Screening for hypertension was done by trained volunteers with the use of validated digital and mercury sphygmomanometers following the MMM protocol. Hypertension was defined as blood pressure (BP) ≥140/90 mmHg or the use of BP-lowering medication. There were 6398 participants (53.0% female) with a mean (SD) age of 41.7 (15.0) years. Hypertension was present in 36.4% of the participants with 51.1% of the hypertensives aware of their status, 41.8% on medication, of whom 43.1% were controlled. Overall, only 18.0% of all hypertensive participants had their BP under control. The proportion with hypertension is high, and awareness, treatment, and control rates are low. Concerted efforts are needed to improve awareness and treatment of hypertension in Nigeria in order to reduce the high rate of complications associated with uncontrolled BP.